Measurement of IL‐12 (p40, p35), IL‐23p19, and IFN‐γ mRNA in Duodenal Biopsies of Cats with Inflammatory Enteropathy. (21st October 2013) - Waly, N.E.; Peters, I.R.; Day, M.J.; Stokes, C.R.; Bailey, M.; Gruffydd‐Jones, T.J.
<x xml:space="preserve">Abstract</x> Background Dietary hypersensitivity and inflammatory bowel disease (IBD) are important causes of chronic vomiting and diarrhea in cats. IL‐23 has been recently found to be a key factor in the immunopathogenesis of IBD in humans but the involvement in IBD has not been investigated in cats. Hypothesis/Objectives Expression of genes encoding Il‐12p35 and p40, IL‐23p19, and IFN‐γ may be up‐regulated in duodenal biopsy specimens taken from cats with histologic evidence of inflammation. Animals and Methods Duodenal biopsy specimens were collected from control cats (n = 21) and cats with inflammatory enteropathy (n = 13). Routine histopathology, immunohistochemistry (IHC), and qRT‐PCR were used to assess expression of MHC class II and to measure gene transcripts encoding the p35, p40, and p19 subunits of the IL‐12 family of cytokines and IFN‐γ. Results There were significant differences in expression of mRNA encoding IL‐12p35 and IL‐23p19 between healthy cats and cats with inflammatory enteropathy. IL‐12p35 mRNA was lower in the duodenal mucosa of cats with inflammatory enteropathy compared with the mucosa of healthy cats (P = .001). In contrast, IL‐23p19 mRNA expression was higher in duodenal biopsy specimens from cats with inflammatory enteropathy than in those from healthy controls (P = .001). There was no difference in expression of IL‐12p40 and IFN‐γ mRNA (P > .05). The majority of cats with inflammatory enteropathy had histologic evidence of moderate to severe colitis (score 2). Conclusions and Clinical Importance The results of this preliminary study suggest that IL‐23 plays a role in the pathogenesis of feline inflammatory enteropathy.